Nonamplification ERBB2 genomic alterations in 5605 cases of recurrent and metastatic breast cancer: An emerging opportunity for anti‐HER2 targeted therapies. Issue 17 (10th June 2016) - Ross, Jeffrey S.; Gay, Laurie M.; Wang, Kai; Ali, Siraj M.; Chumsri, Saranya; Elvin, Julia A.; Bose, Ron; Vergilio, Jo‐Anne; Suh, James; Yelensky, Roman; Lipson, Doron; Chmielecki, Juliann; et al.
Abstract : BACKGROUND: Activating, nonamplification ERBB2 mutations ( ERBB2 mut) are not detected by immunohistochemistry (IHC) or fluorescence in situ hybridization (FISH), but are detected by DNA sequencing and may predict clinical responses to human epidermal growth factor receptor (HER2)‐targeted therapy. The authors queried 5605 advanced/metastatic breast cancers (mBC) to uncover the frequency of ERBB2 mut genomic alterations. Clinical responses to anti‐HER2 therapeutics were identified. METHODS: DNA was extracted from 40 µm of formalin‐fixed paraffin‐embedded (FFPE) sections. Comprehensive genomic profiling (CGP) was used to evaluate up to 315 genes (592× mean coverage depth). Results were analyzed for base substitutions, short indels, copy number changes, and selected rearrangements. RESULTS: Of 5605 cases, 698 (12.5%) featured ERBB2 alterations, including 596 (10.6%) ERBB2 amplifications ( ERBB2 amp) and 138 (2.4%) ERBB2 mut; 38 cases (0.7%) had co‐occurring ERBB2amp and ERBB2mut. ERBB2mut predominantly affected the kinase (124 cases; 90%) or extracellular (15 cases; 11%) domains. Both primary BC (52 cases; 38%) and metastatic site biopsies (86 cases; 62%) were found to harbor ERBB2 mut, which were distributed across carcinoma not otherwise specified (NOS) (69 cases; 50%), invasive ductal carcinoma (IDC) (40 cases; 29%), invasive lobular carcinoma (ILC) (27 cases; 20%), and mucinous mBC (2 cases; 1%). Genes commonly coaltered with ERBB2 were tumor protein 53 ( TP53 ) (49%); phosphatidylinositol 3‐kinase catalytic subunit alpha ( PIK3CA ) (42%); cadherin 1, type 1 ( CDH1 ) (37%); MYC (17%); and cyclin D1 protein ( CCND1 ) (16%). CDH1 mutations were enriched in ERBB2 mut mBC ( P <0.0006) and associated with recurrent mBC. Selected patients with ERBB2 mut, without ERBB2 amp, who responded to anti‐HER2 targeted therapies are presented herein. CONCLUSIONS: Within this large series, 1.8% of cases harbored ERBB2 mut, which are undetectable by standard‐of‐care IHC or FISH tests. Metastatic BC driven by ERBB2 mut respond to anti‐HER2 targeted therapies, and expanding clinical trials designed to detect ERBB2 mut by CGP and optimize targeted treatments are warranted. Cancer 2016 . © 2016 American Cancer Society . Cancer 2016;122:2654–2662. © 2016 American Cancer Society. Abstract : Nonamplification ERBB2 mutations cannot be detected by standard‐of‐care immunohistochemistry or fluorescence in situ hybridization, although the presence of these alterations may predict response to human epidermal growth factor receptor 2‐targeted therapy. In a series of 5605 metastatic breast cancers, 2.4% of all cases and 20% of cases with ERBB2 alterations were found to harbor nonamplification mutations, which represents a substantial patient population who may benefit from human epidermal growth factor receptor 2‐targeted therapies.